Pengaruh Promosi, Daya Tarik Iklan, Dan Celebrity Endorsement Terhadap Minat Beli Konsumen Online Shop Tokopedia (Studi Kasus Pada Mahasiswa FEB Angkatan 2018) - Agus Salim; Nurhajati Nurhajati; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research aims to find out the influence of promotion, advertising power and celebrity endorsement on the buying interest of consumers online shop tokopedia study in students feb Universitas Islam Malang Force 2018. The type of research used is quantitative research with questionnaire dissemination methods. The sample in this study was as many as 100 respondents and data processing using the SPSS computer program. This research has qualified for validity and reliability. The data analysis used in this study is a test of classical assumptions, normality, multiple linear regression, hypothesis test and determination coefficient analysis. The variables used in this study are the Buy Interest variable (dependent variable), while the independent variables are Promotion, Ad Attractiveness and Celebrity Endorsement.The results of this study concluded that Variable Promotion, Ad Attractiveness and Celebrity Endorsements are influential both simultaneously and partially on Consumer Buying Interests. Keywords: Promotion, Ad Appeal, Celebrity Endorsement and Consumer Buying Interest.